PENGABDIAN KEPADA MASYARAKAT (PKM) KETAHANAN PANGAN PEDESAAN KERTHALANGU DENPASAR TIMUR - I Nyoman Winyana; Ni Made Indah Resiyana Putri (UNHI Press, 2021)
Community service is one of the important commitments made by universities in the context of blending in with the community. The existence of academics in the development of rural communities is at the same time a measure of the existence of universities in collaborating with rural communities. One form of PKM carried out by the Unhi campus community in 2021 is to build a village to care for the earth. Through the thematic KKN 2021, namely the village of kala Tatwa 'Ausadhining Bumi' which means glorifying plants on earth with the concept of